Pengaruh Kualitas Produk, Word Of Mouth Dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Tas Texas Collection Ditoko Texas Collection Jakarta Timur - Arum Fitri Nuryanti; Suadi Sapta Putra; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of the t test on the variables of product quality, word of mouth and customer satisfaction on purchasing decisions for Texas Collection bags at the texas collection shop in East Jakarta. This research data source uses primary data in the form of a questionnaire, this research data was given to 97 respondents who made purchasing decisions for Texas Collection East Jakarta. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics that have been processed by SPSS 26. The results showed that product quality (Xl) has a positive and significant influence on purchasing decisions. This can be seen from the results of the t test where ting (2.814> 1.984) Word of Mouth variable (X2) has a positive and significant influence on purchasing decisions. This can be seen from the t test results where ting (5.377> 1.984). The Customer Satisfaction variable (X3) has a positive and significant influence on purchasing decisions. This can be seen from the t test results where ting (2.411 > 1.984). Keywords: Product Quality, Word of Mouth and Customer Satisfaction.